Konsep Open-plan pada Rumah Tinggal: Studi Kasus, Rumah di Gg.Ramdhan II 128/47, Bandung - Arliana, Alfira; selma, arina nada; Nugroho, Ardianto (Program Studi Desain Interior Unikom, 2021)
The need for land to build houses in densely populated cities is increasingly limited and has very high prices, so many people build houses by maximizing the use of land area, but still upholding the aesthetics and comfort. To realize this, one way is to apply the open plan concept in house design. The purpose of this article is to prove that the open-plan concept can emphasize the area of ​​​​a minimalist house and can also have a good circulation of activities, without worrying about a small area. Through this article, the author will provide a description of residential houses that have applied the open plan concept using qualitative methods through a case study approach. This study will also discuss the advantages and disadvantages that are adapted to the function of the house accordance with existing research.